A comparison of fine wire insertion techniques for deep finger flexor muscle electromyography. (August 2018) - Heales, Luke J.; Tucker, Kylie; Vicenzino, Bill; Hodges, Paul W.; MacDonald, David A.
Abstract: Introduction: Intramuscular electromyography electrodes targeting flexor digitorum profundus (FDP) are inserted via the anterior or medial aspect of the forearm. These two methods pose different risks to neurovascular structures which overly FDP. This study aimed to compare the insertion depth and consider advantages and limitations of two different techniques to insert intramuscular electrodes into FDP. Methods: Using ultrasound imaging, neurovascular structures were identified along the path of FDP electrode insertion at the junction of the proximal and middle third of the ulna, bilaterally, in ten healthy individuals. Insertion depth was compared between the anterior and medial approaches for the mid muscle belly and targeted insertion to the index finger fascicle of FDP. Results: In our sample the ulnar artery was superficial to the FDP muscle when viewed anteriorly and was beyond the furthest border of FDP when viewed medially. Compared to the anterior approach, the medial insertion depth was 1.5 cm (95%CI 1.4–1.7, p < 0.001) less to the mid-belly of FDP and 0.6 cm (95%CI 0.4–0.7, p < 0.001) less to the index finger fascicle of FDP. Discussion: The medial approach involves less depth and lower risk for perforation of neurovascular structures when inserting intramuscular electrodes into the FDP muscle.